PEMANFAATAN MEKANISME ASEAN DALAM PENYELESAIAN MASALAH PERBATASAN THAILAND - C.P.F. Luhulima (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2014)
AbstractThailandâ€™s borders with Myanmar, Laos, Cambodiaand Malaysia have been established through amapping process within the framework of theTreaty of Westfalpha. Since the England andFrance left Southeast Asia after World War II,Thailand questioned its borders with itsneighbouring countries and since then the borderissue between Thailand and her neighboursbecame the major issue. The attempts to resolvethe border conflict between Thailand andMyanmar have been conducted throughâ€œconstructive engagementâ€, and through her policyof â€œchanging battlefields to market placesâ€. TheASEAN approach has been employed in her borderconflict with Cambodia. Cambodiaâ€™s attempt toinvolve the UN Security Council has been respondedby the Council to involve ASEAN in its resolution.The failure of the ASEAN approach made Cambodiato submit the issue to the ICJ in The Hague in April2011. On November 11, 2013 ICJ decided thatPreah Vihear and its surrounding area belong toCambodia. The source of the conflict with Malaysiawas not primarily about border, but it was apolitical complaint. The rebellion at the border areawill thus not terminate until the Thai authoritiesunderstand the complaints of the Muslim-Malaysat the border area. The ASEAN mechanism toresolve the inter-state conflict consists of bilateral,trilateral approaches, through the High Council andthe United Nations. The application of stepsbetween Thailand and its neighbours are thebilateral, trilateral steps and the one through theInternational Courtof Justice in The Hague.Keywords: Thailand, Myanmar, Malaysia, Kamboja,ASEAN, Dispute Settlement Mechanism AbstrakBatas Kerajaan Thailand dengan Myanmar, Laos,Kamboja dan Malaysia dibentuk melalui prosespemetaan di dalam kerangka Traktat Westfalia.Ketika Inggris dan Prancis mengundurkan dirisesudah Perang Dunia II, Thailand mempersoalkanperbatasannya dengan negara-negara tetangganya,sehingga perbatasan menjadi pokokpermasalahan. Sengketa dengan Myanmar diupayakanpenyelesainnya melalui â€œconstructiveengagementâ€, dan dengan kebijakannya â€œchangingbattlefields to market placesâ€. Pendekatan ASEANdigunakan untuk menyelesaikan konflik denganKamboja. Pelibatan Dewan Keamanan PBB dijawabdengan meminta kedua belah pihak melibatkanASEAN. Kegagalan pendekatan ASEAN menyebabkanKamboja mengajukan kasus ini ke ICJ padaApril 2011. Pada 11 November 2013 MahkamahInternasional di Den Haag memutuskan bahwaCandi Preah Vihear dan wilayah sekitarnya adalahmilik Kamboja. Permasalahan dengan Malaysiabukanlah masalah perbatasan antara keduanegara melainkan keluhan politik, sehinggapemberontakan di perbatasan tidak akan berakhirsampai penguasa Thailand memahami keluhanorang-orang Muslim-Melayu di perbatasan.Mekanisme ASEAN untuk mengatasi sengketaantarnegara anggota terdiri dari langkah bilateral,trilateral, melalui pembentukan Dewan Tinggi danmelalui lembaga hukum PBB. Yang di-terapkandalam kasus sengketa perbatasan antara Thailanddan negara tetangganya ialah pendekatanbilateral dan trilateral serta melalui LembagaPeradilan PBB.Kata kunci: Thailand, Myanmar, Malaysia,Kamboja, ASEAN, Mekanisme PenyelesaianPerselisihan